From the bakery to the brain business: developing inducible yeast models of human neurodegenerative disorders. (October 2008) - Ocampo, Alejandro; Barrientos, Antoni
In the last decade, the budding yeast Saccharomyces cerevisiae has been used as a model system to study the mechanisms of the human aging process and of age-associated neurodegenerative disorders such as Parkinson's, Huntington's, Alzheimer's, and amyotrophic lateral sclerosis. S. cerevisiae is a facultative aerobic, unicellular yeast, and despite their simplicity, yeast cells possess most of the same basic cellular machinery as neurons in the brain, including pathways required for protein homeostasis and energy metabolism. The power of yeast genetics and the use of high-throughput screening technologies have provided important clues concerning the pathophysiology of these disorders and the identification of candidate therapeutic targets and drugs. The yeast models are based on the expression of human disease proteins in yeast and recapitulate some of the cytotoxic features observed in patients. However, the currently available models mostly suffer from high-level protein expression that results in acute cytotoxicity, and from metabolic constraints when the models are based on extensively used, strong, galactose-inducible promoters. The models would increase their significance if they were based on continuous and tightly regulated gene expression systems for both activation and levels of expression. This would allow for more chronic cytotoxicity that better simulates the timing of events that occur during disease progression. Additionally, the use of metabolism-independent inducers would allow for the study of cell toxicities under conditions where the cells are forced to exclusively respire, thus more reliably modeling the highly oxidative neuronal metabolism. Here we have constructed yeast models of Huntington's disease based on the expression, under the control of different promoters, of the first exon of the huntingtin-containing polyglutamine tracts of both wild-type and mutant lengths. The different models are compared and evaluated.